4D printing of mechanically robust PLA/TPU/Fe3O4 magneto-responsive shape memory polymers for smart structures - Liu, H.; Wang, F.; Wu, W.; Dong, X.; Sang, L.
The integration of magneto-responsive shape memory polymers (SMPs)into 4D printing provides novel opportunities to create innovative and intelligent products controlled in a contactless method. In this study, a promising SMPs with robustly mechanical property and magneto-responsive behavior were proposed and fabricated into 3D printing feedstock based on polylactic acid (PLA), thermoplastic polyurethane (TPU)and Fe3O4 particles. Results revealed that the 3D-printed PLA/TPU/Fe3O4 possessed robust tensile strength and modulus with a homogeneous distribution of magnetic particles in polymer blends. Also, PLA/TPU/Fe3O4 exhibited excellent shape fix ratio (?100 percent), recovery ratio (>91 percent)and rapid magnetic response within as short as 40 s, suggesting the high efficiency of heat generation by magnetic particles. Moreover, smart structures including honeycomb and bionic flower-like model were designed and printed as an original shape. After programmed by an external force, the folded lattice structure at the temporary shape could recovered completely under a contactless magnetic field. The flower-bud structure sequentially restored layer-by-layer controlled by using three pedals with varied Fe3O4 composites. Consequently, the high-load capacity, fast magneto-responsive behavior and high recovery performance of the proposed multi-material have great potentials in actuator or robots applications via 3D printing.
Keywords: 4D PRINTING; SHAPE MEMORY EFFECTS; FE3O4 PARTICLES; MAGNETO-RESPONSIVE STRUCTURES